Microstructures and Corrosion Behaviors of an Austenitic Stainless Steel Strengthened by Nanotwinned Austenitic Grains1 . Issue 4 (19th October 2015) - Yan, Fengkai; Tao, Nairong; Pan, Chen; Liu, Li
Abstract : A novel type of nanotwinned austenitic stainless steel consisting of the nanotwinned grains embedded in coarsened nano‐sized grains and recrystallized matrix was synthesized. Potentiodynamic polarization measurements indicate that the nanotwinned samples exhibit a higher passive ability in the acidic solution and a comparable pitting resistance in chloride solution in comparison with that of their coarse grained counterparts. The effects of the microstructure, specifically the presence of nanotwinned grains, on the corrosion resistance are discussed. The nanotwinned austenitic stainless steel possesses an excellent combination of strength and ductility as well as corrosion resistance. Abstract : In this paper, the authors synthesize a novel type of nanotwinned austenitic stainless steel mainly consisting of nanotwinned grains embedded in recrystallized matrix. Polarization measurements indicate that introduction of nanotwins do not deteriorate the corrosion resistance. The nanotwinned grains seem to promote the growth rate of passive film while do not compromise the pitting resistance.